Autonomy of urban planning law and its fundamental principles (Revista do Tribunal Regional Federal da 3ª Região, 2018)
There has been an intense doctrinal discussion on the autonomy of urban law. Most of the doctrine followers understand it as just a section of administrative law, while, for other authors, that field of public law would have already won its legal /positive and scientific autonomy. This paper presents arguments for the latter stance. Based on studies of the historical evolution of normative urban law systems, both in European countries and in Brazil, it appears that the Government is not limiting itself to only lay down rules concerning construction policies (regulatory urbanism), i.e., standards that simply prescribe administrative restrictions to urban property. In fact, the intervention of the Government in urban matters has ceased to be merely a constraining one. The Administration has assumed – as far as early twentieth century - an active role in urban planning (operational urbanism). This led to repercussions for urban law, especially with regard to its autonomy from other fields of public law. Hence the indication for specific rules and principles to regulate the activity of organization of urban space in several legal systems of European countries. Brazil followed suit, especially based on the Federal Constitution of 1988 and after the enactment of the City Statute (Law 10.257/2001), whose article 2 presents a list of fundamental principles of urban policy. The indication of such fundamentals, which are covered in this work, reinforces the thesis that defends the scientific autonomy of urban law.
Keywords: Urban Law; autonomy; City Statute; major principles